"Soy tú. Soy él": African Immigration and Otherness in the Spanish Collective Conscience - Michael Ugarte (Studies in 20th & 21st Century Literature, 2006)
The commonly heard statement "Spain is different" contains a series of contradictions, paradoxes, and questions concerning Iberia's place within the global community, a community that is itself deeply contradictory—more and more the same and yet more and more fragmented. Immigration highlights the sameness/otherness dichotomy in Spanish culture, and the situation of African immigrants has especially caused the Spanish national consciousness an ethical quandary. Here I examine four recent cultural representations of African immigration in Spain—two journalistic works: Mikel Azurmendi's Estampas del Ejido and Antonio Elorza's articles in El País; and two documentary films: Básel Ramsis's El otro lado: un acercamiento a Lavapiés and José Luis Guerín's En construcción in order to assess the ways in which Spaniards are projecting their sense of national identity in the face of large-scale immigration, a most revealing mirror.
Keywords: Iberia; global community; Spain; Latin America; fragmentation; immigration; sameness; otherness; Spanish culture; African immigrants; ethics; Mikel Azurmendi; Estampas del Ejido; Antonio Elorza; El País; Básel Ramsis; El otro lado: un acercamiento a Lavapiés; JoséLuis Guerín; En construcción; national identity